Lumiracoxib for acute postoperative dental pain: a systematic review of randomized clinical trials - Silva, Ricardo Carvalho Lopes (2011)
CONTEXT AND OBJECTIVE: Lumiracoxib is an anti-inflammatory drug that has been used to treat acute dental pain, mainly in postsurgical settings, in which the greatest levels of pain and discomfort are experienced during the first 24 hours. This study aimed to assess the efficacy and safety of lumiracoxib for treating acute postsurgical dental pain. DESIGN AND SETTING: Systematic review developed at the Brazilian Cochrane Centre, Universidade Federal de São Paulo. METHODS: An electronic search was conducted in the PubMed, Cochrane Library, Lilacs (Literatura Latino-Americana e do Caribe em Ciências da Saúde), SciELO (Scientific Electronic Library Online) and Embase databases. A manual search was also performed. Only randomized controlled trials were included, and these were selected and assessed by two researchers with regard to the risk of bias. RESULTS: Three clinical trials with 921 participants were included. Lumiracoxib 400 mg produced onset of analgesia in a shorter time than shown by lumiracoxib 100 mg, celecoxib 200 mg and ibuprofen 400 mg. There was no difference between lumiracoxib 400 mg and rofecoxib 50 mg. In two studies, the mean time taken to attain onset of analgesia for the placebo was not estimated because the number of participants who reached onset was too small. CONCLUSION: There is evidence with a moderate risk of bias that recommends the use of lumiracoxib for acute postoperative dental pain. However, the adverse effects are not completely known. Given that lumiracoxib is currently available in only three countries, further studies are likely to be rare and discouraged.